Birgit Sawyer. Property and Inheritance in Viking Scandinavia, the Runic Evidence. Occasional Papers on Medieval Topics, 2. Viktoria Bokförlag, 1988). 47 s. + VI Tbles. 35 Sv.kr. - Linton, Michael (Historie/Jyske Samlinger, 1991)
-